(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to identify the most important features and details of the deposit guarantee system, which is one of the most important topics that gained great importance on the banking scene after the financial crises that many countries witnessed, which led to the failure of many banks, as the deposit guarantee system contributes to achieving stability for financial institutions and reducing the aggravation of... Economic problems resulting from bank insolvency and default and the factors that affect it, and developing audit procedures in accordance with international auditing standards for the Deposit Insurance Company in a way that leads to strengthening the procedures followed in auditing the company, The researchers reached a set of conclusions, the most prominent of which is that establishing a deposit guarantee system increases the degree of stability of deposits and works to attract more savings and increase cash flows to the banking system, enhances its ability to invest and lend, and has an effective contribution to reducing the risks that threaten the depositor public in critical circumstances. Thus, increasing demand for deposits, as well as reassuring depositors and increasing savings awareness, The approved audit program does not meet the requirements contained in international auditing standards. Therefore, developing a specialized audit program in accordance with the requirements of international auditing standards helps the auditor in obtaining appropriate evidentiary evidence that will help him express an opinion on the financial statements. Accordingly, the researchers proposed several recommendations, the most important of which is adopting the prepared audit program. By the researcher in accordance with the requirements of international auditing standards when auditing a deposit insurance company.